Water marginality in rural and peri-urban communities - Adeyeye, Kemi; Gibberd, Jeremy; Chakwizira, James (Journal of cleaner production, 2020)
Water supply in an increasing number of rural and peri-urban communities can be described as marginal i.e. subject to failure, becoming unaffordable or increasingly difficult to access. A range of common factors contribute to water marginalisation or access bias. Firstly, communities may be poorly served by formal water infrastructure by being on the margins of urban settlements. Secondly, where water infrastructure exists, this may be prone to failure as local municipalities and water utilities with limited capacity and resources struggle to maintain a widely dispersed system. Thirdly, when local water systems fail, they are often not repaired quickly, if repaired at all. This results in people, often with very limited resources having to obtain water from far distances or having to pay someone to transport water to them in order to meet their basic water needs. Thus, where water supplies are unreliable, unaffordable and difficult to access, geography, urban settlement patterns, the choice of water distribution systems, and the management capacity result in water marginality. This paper investigates water marginality in communities in rural and peri-urban areas in South Africa. It utilises surveys and interviews of communities, the local authority, water and urban planning officials, to understand the nature of this marginality, and investigates the key contributory factors. This forms the basis for recommendations on how access and marginalisation challenges can be addressed. The paper provides valuable insights on how, and why, water marginality occurs, and proposes strategies for sustainable solutions. As climate change and rural-urban migration accentuate water marginality, the study offers important and timely insights in an area that urgently requires further research.